A history of the Qwathi people from earliest times to 1910 - Ndima, Mlungisi (Rhodes University, Faculty of Humanities, Department of History, 1989)
This is the first history of the Qwathi to appear. It relates all the events which have shaped the historical consciousness of the Qwathi people. The first chapter deals with the foundation of the Qwathi chiefdom by Mtshutshumbe and his followers who emigrated from EmaXesibeni to Thembuland before 1700. It also covers the development of the various Qwathi clans. The reign of Fubu which is discussed in Chapter Two was characterised by warfare. The most important of these wars was the Qwathi-Thembu war of the beginning of the nineteenth century. Its importance lies in the fact that although the Qwathi were a small chiefdom, they were able to goad the Thembu nation into war, the results of which were indecisive, hence, in subsequent years, the Thembu were always cautious in their dealings with the Qwathi. Fubu's other wars, including those of the Mfecane, are also discussed. Chapter Three deals mainly with the Qwathi-Thembu relations during the reign of Dalasile, Fubu's son. These were at first cordial but they became strained when Ngangelizwe took over as Thembu king in 1863. Dalasile refused to involve the Qwathi people in Thembu conflicts with their enemies and he desired to pursue an independent line. In 1875, when Ngangelizwe accepted colonial control, Dalasile stood out against it but, under pressure from the agents of colonialism, he gave in. The period from 1875 to 1880 was one of passive resistence to colonial control. This erupted into Dalasile's rebellion against the colony from 1880 to 1881. Chapter Six deals with the surrender, relocation and the introduction of a new system of control called the "Ward System". The ruling house was replaced by appointed headmen most of whom were drawn from non-Qwathi communities. Chapter Seven deals with the rise and Fall of the Qwathi peasantry. The fall of the peasantry facilitated labour migracy which contributed to further deterioration of the Qwathi both economically and physically.
Keywords: Qaba (African people) -- History